The Training on the use of Phet and Pascal Applications to Enhance Critical Thinking Skills and Physics Learning Outcomes for Students of SMAN 1 Gunungsari, West Lombok - Taufik, Muhammad; Susilawati, Susilawati; ‘Ardhuha, Jannatin; Hikmawati, Hikmawati; Verawati, Ni Nyoman Sri Putu (Unram Journal of Community Service, 2024)
The training program is intended to provide SMAN 1 Gunungsari, West Lombok students the abilities they need to use the PhET and Pascal software efficiently. The main goals of the training are to provide students with the skills necessary to use and navigate these programs efficiently to improve physics learning results. Participants will learn how to use the PhET and Pascal software to conduct physics experiments, depict difficult ideas, and solve demanding issues through an organized training program and interactive sessions. The training will also emphasize helping students strengthen their critical thinking abilities as they investigate the connections between theoretical concepts and actual experiences. The program will include several practical exercises and demonstrations to ensure that students not only learn the theory but also have the practical skills necessary to use PhET and Pascal successfully. It is expected that these abilities would improve their physics learning process overall. After the training, students will be required to demonstrate improved PhET and Pascal skills, as well as their ability to independently study physics principles, conduct experiments, and use critical thinking to solve problems. As students utilize the potential of these strong tools for learning, this training program signifies an important milestone in empowering them to achieve success in their physics studies as well as afterwards.